2011
DOI: 10.1016/j.jnoncrysol.2010.10.039
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ce codoping and H2 pre-loading on Er/Yb-doped fiber: Radiation response characterized by Confocal Micro-Luminescence

Abstract: International audienceConfocal microscopy luminescence measurements were applied to study the X-ray radiation response of Er/Yb-doped optical fibers in connection with H2 pre-loading and with the addition of another lanthanide element (Cerium) in the core composition. Laser excitations at 488 nm and 325 nm allow deriving the emission and absorption pattern of Er3+, the latter derived from the dips appearing in a wide luminescence band related to defects in silica. We found that the luminescence spectrum of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The main difference between the two fibers is the addition of Cerium (Ce) ions in the core of fiber J. As expected from our previous work [14][15], this element strongly affects the radiation sensitivity of RE-doped glasses without degrading its amplification performance. Fig.1 illustrates the attenuation spectra of the two fibers before irradiation, measured by the cut-back method through excitation of the DC in the multimode regime with a white light source.…”
Section: A Tested Optical Fibers and Amplifiersmentioning
confidence: 83%
“…The main difference between the two fibers is the addition of Cerium (Ce) ions in the core of fiber J. As expected from our previous work [14][15], this element strongly affects the radiation sensitivity of RE-doped glasses without degrading its amplification performance. Fig.1 illustrates the attenuation spectra of the two fibers before irradiation, measured by the cut-back method through excitation of the DC in the multimode regime with a white light source.…”
Section: A Tested Optical Fibers and Amplifiersmentioning
confidence: 83%
“…The processes, involved at irradiating the fibers with the result being rise followed by saturation of IA, described by the "stretched-exponent" law [14,24,26]), comprise: (i) creating of secondary carriers (holes h + and electrons e − ) in the core-glass matrix by β (primary) electrons and their trapping on such glass imperfections as Ce ions (Ce 3+ /Ce 4+ ), nonbridging oxygen centers, other centers associated with Al and P, and oxygen vacancies; (ii) direct h + …e − recombination (annihilation); (iii) thermally or/and radiatively activated recombination between the centers or defects that have arisen during and after β-irradiation. Concerning the role of Ce-doping, we assume that IA is produced via irradiation-induced reactions Ce 3+ +h + →Ce 3+ h + (→?Ce 4+ ) and Ce 4+ +e − →(?Ce 4+ e − )→Ce 3+ [26][27][28], implying Ce was in valences 3+/4+ in pristine fibers or/and being generated via irradiation. Note that determination of relative contents of Ce 3+ /Ce 4+ ions in the pristine state is hard and that at low Ce doping, mainly fluorescing Ce 3+ are formed in the core-glass, while at higher overall Ce concentration both Ce 3+ and Ce 4+ (nonfluorescing) ions can be present.…”
Section: β-Irradiated Fibersmentioning
confidence: 99%
“…1. The main difference is the addition of Cerium (Ce) ions in the core of RH sample that strongly enhances its radiation tolerance [14], [15], [20]. Fig.…”
Section: A Tested Optical Fibers and Amplifiersmentioning
confidence: 99%
“…Jin Ma et al [13] observed a complete darkening of the output power of their Er/Yb amplifiers after an irradiation dose of few dozens of krad. More recently, our group demonstrated the efficiency of Cerium-codoping in the core of Er/Yb doped optical fibers to improve their radiation tolerance [14], [15], such Ce-positive effect was also observed on fibers solely doped with Yb or Er [16], [17]. This radiation hardening by component approach leads to an amplifier with identical optical characteristics, before irradiation, to the ones designed with a standard RE-fiber (gain of 19 dB) but associated with a very limited radiation-induced gain decrease of dB after a dose of krad.…”
Section: Introductionmentioning
confidence: 99%